2021
DOI: 10.1088/1361-6404/abd4c8
|View full text |Cite
|
Sign up to set email alerts
|

An approach to the magnetic field of a finite solenoid with a circular cross-section

Abstract: We present a simple approach, different from approaches in the literature, for calculating the magnetic field of a finite solenoid with a circular cross section, carrying an ideal surface current with an ordinary azimuthal component and a small axial component due to nonideal winding. The results are given as an infinite series whose terms are elementary functions or simple polynomials rather than other infinite series. It is easy to deal with the results because the polynomials involved are partial binomial e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…A different approach was shown in refs. [97] to [72] or [73], using a non-standard polynomial series for the field result of a shell, with an analysis on convergence. An analytic solution from a radial integration of the shell was not found, and instead an analytic approximation was given as with other previous work.…”
Section: Volumementioning
confidence: 99%
“…A different approach was shown in refs. [97] to [72] or [73], using a non-standard polynomial series for the field result of a shell, with an analysis on convergence. An analytic solution from a radial integration of the shell was not found, and instead an analytic approximation was given as with other previous work.…”
Section: Volumementioning
confidence: 99%
“…Based on this principle, a magnetic field of arbitrary strength can be generated according to the test specimen and test conditions, where the strength of the magnetic field depends on the type of core, turn diameter, turn number, magnetic path (core shape), and input current magnitude [ 18 , 19 ].…”
Section: Theoretical Background About Em Sensormentioning
confidence: 99%
“…Several authors have reported analytical and numerical proofs for it [3][4][5][6][7][8], but there are still many students hardly understand the explanations. In this paper, we describe a more detailed explanation to answer why the magnetic field outside the ideal solenoid is zero.…”
mentioning
confidence: 99%